1995
DOI: 10.1159/000217951
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin Fragment 21-1 in Gynecologic Malignancy: Comparison with Cancer Antigen 125 and Squamous Cell Carcinoma-Related Antigen

Abstract: We measured serum cytokeratin fragment 21–1 (CYFRA 21–1) levels by a solid-phase immunoradiometric assay in 102 healthy Japanese women, and set the reference value at 1.9 ng/ ml (mean +2 SD of the serum levels based on a linear distribution). Pretreatment serum CYFRA 21–1 levels were also analyzed in 235 women with benign (n = 94) or malignant (n = 141) gynecologic disease, and were compared with the serum levels of CA 125 and SCC. The respective positivity rates for CYFRA 21–1 and CA 125 were 64.0 and 77.2% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Mobus et al (27) found that ovarian cancer cell lines express large amounts of cytokeratin 19, suggesting that overexpression of cytokeratin 19 paralleled ovarian carcinogenesis. Few data are currently available in the literature about the clinical relevance of serum CYFRA 21-1 assay in the management of patients with ovarian cancer (12,13,22) . By assessing pretreatment serum tumor marker levels in 235 women with different gynecologic diseases, Inaba et al (13) observed that positivity rates for CYFRA 21-1 (cut-off = 1.9 ng/ml) were 64.0% in ovarian malignancy compared with 4.2% in benign ovarian masses.…”
Section: Serum Cyfra 21-1 In Ovarian Cancer Patients 279mentioning
confidence: 99%
See 3 more Smart Citations
“…Mobus et al (27) found that ovarian cancer cell lines express large amounts of cytokeratin 19, suggesting that overexpression of cytokeratin 19 paralleled ovarian carcinogenesis. Few data are currently available in the literature about the clinical relevance of serum CYFRA 21-1 assay in the management of patients with ovarian cancer (12,13,22) . By assessing pretreatment serum tumor marker levels in 235 women with different gynecologic diseases, Inaba et al (13) observed that positivity rates for CYFRA 21-1 (cut-off = 1.9 ng/ml) were 64.0% in ovarian malignancy compared with 4.2% in benign ovarian masses.…”
Section: Serum Cyfra 21-1 In Ovarian Cancer Patients 279mentioning
confidence: 99%
“…Different cytokeratins have been found in human epithelia and have been divided into two subfamilies: basic (cytokeratins [1][2][3][4][5][6][7][8] and acidic (cytokeratins [9][10][11][12][13][14][15][16][17][18][19][20], which can be distinguished on the basis of immunological, peptide mapping, mRNA hybridization, and primary amino acid sequence data (3,4) . Cytokeratin fragments exist also in soluble form and can be detected in the serum with the aid of monoclonal antibodies (5) .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…When present in peripheral blood, cytokeratins are mainly detected as partially degraded, single protein fragments or complexes. A fragment of CK19, Cytokeratin fragment 21-1 (CYFRA 21-1), has been extensively studied in patients with non-small cell lung, esophageal cancer and gynecological malignancy where it has been shown to be a clinically useful prognostic and monitoring marker [16][17][18].…”
mentioning
confidence: 99%